2017
DOI: 10.1159/000484084
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Emergency Room Visits in Intestinal Behçet’s Disease

Abstract: Background/Aims: Intestinal Behçet’s disease (BD) is a chronic recurring intestinal vasculitic disorder that can lead to emergency room (ER) visits. We aimed to investigate the independent risk factors associated with intestinal BD-related ER visits. Methods: We retrospectively reviewed 606 patients with intestinal BD registered at the Inflammatory Bowel Disease Clinic of Severance Hospital, Seoul, Korea. Results: One hundred eighty-five patients (30.5%) visited the ER at least once (total visits, 510). In mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
2
0
3
Order By: Relevance
“…Based on reports of the 5‐year course of intestinal BD, 74.6% of patients experience remission or mild disease activity, and 16.2% have multiple relapses or chronic symptoms 8 . Similar to inflammatory bowel disease (IBD), intestinal BD can present with perforation, peritonitis, or severe lower gastrointestinal bleeding requiring medical acceleration, intestinal surgery, hospitalization, or emergency room visits 9–13 . In a 10‐year follow‐up study, there were no differences in the cumulative probabilities of intestinal surgery, hospitalization, recurrence, and reoperation rates between Crohn's disease (CD) ( n = 332) and intestinal BD ( n = 276) 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on reports of the 5‐year course of intestinal BD, 74.6% of patients experience remission or mild disease activity, and 16.2% have multiple relapses or chronic symptoms 8 . Similar to inflammatory bowel disease (IBD), intestinal BD can present with perforation, peritonitis, or severe lower gastrointestinal bleeding requiring medical acceleration, intestinal surgery, hospitalization, or emergency room visits 9–13 . In a 10‐year follow‐up study, there were no differences in the cumulative probabilities of intestinal surgery, hospitalization, recurrence, and reoperation rates between Crohn's disease (CD) ( n = 332) and intestinal BD ( n = 276) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Similar to inflammatory bowel disease (IBD), intestinal BD can present with perforation, peritonitis, or severe lower gastrointestinal bleeding requiring medical acceleration, intestinal surgery, hospitalization, or emergency room visits. [9][10][11][12][13] In a 10-year follow-up study, there were no differences in the cumulative probabilities of intestinal surgery, hospitalization, recurrence, and reoperation rates between Crohn's disease (CD) (n = 332) and intestinal BD (n = 276). 14 Conversely, several studies have reported that prognosis is worse in intestinal BD than in CD.…”
Section: Introductionmentioning
confidence: 99%
“…В табл. 7 представлена терапия в зависимости от тяжести ПКББ, согласно анализу ретроспективных исследований [45,[53][54][55][56][57][58][59].…”
Section: лечениеunclassified
“…[27] за 80 пациентами с ПКББ было установлено, что отсутствие заживления слизистой оболочки кишечника в момент клинической ремиссии является независимым предиктором рецидива ББ [27]. Заживление слизистой оболочки кишечника является важным прогностическим фактором и ассоциируется с длительной клинической ремиссией и снижением частоты госпитализации и хирургических вмешательств [58].…”
Section: лечениеunclassified
See 1 more Smart Citation